Conjugated coordination polymer / ionic liquid composite material as well as preparation method and application thereof

By combining the ionic liquid with the catalyst catalyst of the co -pyramid, adjust the micro -environment of the electrode surface, solve the problem of catalyst activity and selectivity in electrical nitrogen restoration technology, and achieve efficient ammonia production.

CN119332275APending Publication Date: 2025-01-21JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460083.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing electrocatalytic nitrogen reduction technology, the high dissociation energy and low solubility of nitrogen molecules, as well as competitive hydrogen evolution side reactions, limit the activity and selectivity of the catalyst.

Method used

By performing a strong electronic interaction with the catalyst of the ionic liquid with the co -pyramidal polymer, modify the catalyst, adjust the micro -environment of the electrode surface, and build a hydrophobic electrode surface, thereby enhancing the activity of the electrical nitrogen reaction.

Benefits of technology

High catalytic activity and selectivity for the electrocatalytic nitrogen reduction reaction were achieved, and the ammonia yield and Faradaic efficiency were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332275A_ABST
    Figure CN119332275A_ABST
Patent Text Reader

Abstract

The invention provides a conjugated coordination polymer / ionic liquid composite material and a preparation method and application thereof.The preparation method comprises the steps that metal salt, ligand and ionic liquid serve as reactant raw materials and are ultrasonically dispersed in water respectively and mixed to be uniform to obtain a reaction precursor, then ammonia water is added to promote coordination of nickel salt and ligand to obtain a conjugated coordination polymer, and the conjugated coordination polymer / ionic liquid composite material is obtained; strong electron interaction is formed between the ionic liquid and the conjugated coordination polymer, and finally the conjugated coordination polymer / ionic liquid composite material is obtained. The positive ions of the ionic liquid in the obtained composite material are dispersed, mixed and tightly combined with the conjugated coordination polymer, so that the construction of a hydrophobic surface microenvironment can be realized, and the electrocatalytic activity and the selectivity of the hydrophobic surface microenvironment are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conjugated coordination polymer materials and relates to a conjugated coordination polymer / ionic liquid composite material and a preparation method and application thereof. Background Art

[0002] Ammonia is a vital chemical feedstock for modern agriculture, textiles, pharmaceuticals, and plastics production, and is also an ideal hydrogen energy carrier. Currently, nearly 90% of ammonia is produced via the traditional Haber-Bosch process, which involves reacting nitrogen and hydrogen at high temperatures (>400°C) and high pressures (>200 atm). This process not only consumes significant amounts of energy but also results in large-scale carbon dioxide emissions due to the use of natural gas reforming to produce the required H2. Therefore, the development of low-energy electrocatalytic methods for synthesizing ammonia is of great significance.

[0003] Electrocatalytic nitrogen reduction is a potential green ammonia synthesis technology that can be carried out at room temperature and pressure. However, the high dissociation energy of nitrogen molecules (941 kJ mol -1 ) and its low solubility in aqueous electrolytes, as well as the limitation of competitive hydrogen evolution side reaction, limit the improvement of electrocatalytic nitrogen reduction catalytic activity. Developing highly active and selective nitrogen reduction catalysts is an effective way to solve this problem.

[0004] Conjugated coordination polymers (CCPs) have attracted widespread attention in the field of electrocatalysis due to their advantages, such as strong structural designability, excellent conductivity, and large specific surface area. While structural design of CCP catalysts can enhance their catalytic activity, simultaneously improving both activity and selectivity remains a challenge.

[0005] Ionic liquids are sour and It is composed of alkali and is liquid at ambient temperature. It has reversible proton transport properties, is easy to prepare, has low viscosity, and is environmentally friendly. It has high solubility for various gaseous reactants, faster gas diffusion ability, synergistic catalytic effect, and the ability to inhibit the recombination of active hydrogen species. It is considered to be a promising chemical substance for optimizing the local environment of the catalyst. Studies have found that changing the local environment of the catalyst surface can effectively promote the overall reaction process. Combining ionic liquids with conjugated coordination polymer catalysts through strong electronic interactions, modifying the catalyst and then regulating the electrode surface microenvironment is expected to achieve the purpose of enhancing the activity of the electrocatalytic nitrogen reduction reaction. The present invention designs and synthesizes a conjugated coordination polymer / ionic liquid composite material, which exhibits excellent electrocatalytic nitrogen reduction performance. Summary of the Invention

[0006] Purpose of the invention: In response to the problems and shortcomings of the prior art, the present invention provides a conjugated coordination polymer / ionic liquid composite material and its preparation method and application. The preparation conditions are mild, the strong electronic interaction between the cations in the ionic liquid and the conjugated coordination polymer, and the construction of the hydrophobic electrode surface microenvironment enable the prepared conjugated coordination polymer / ionic liquid composite material to have high catalytic activity for the electrocatalytic nitrogen reduction reaction.

[0007] The first aspect of the present invention is to provide a conjugated coordination polymer / ionic liquid composite material, wherein the conjugated coordination polymer / ionic liquid composite material is formed by combining a conjugated coordination polymer and an ionic liquid through strong electronic interaction, wherein:

[0008] The conjugated coordination polymer is constructed by metal single atoms and conjugated organic ligands, wherein the metal single atoms include at least one of iron, cobalt, nickel, copper, and zinc, and the conjugated organic ligands include at least one of 1,2,4,5-benzenetetramine tetrahydrochloride, 2,3,6,7,10,11-hexamethylenetriphenyl, 2,5-diamino-1,4-dihydroxybenzene, dopamine hydrochloride, and pyridine.

[0009] The ionic liquid includes at least one of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, N-butylimidazolium bis(trifluoromethylsulfonyl)imide, and 1-carboxybutyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0010] In one embodiment, the conjugated coordination polymer / ionic liquid composite material has a nanorod morphology with a size of 50-100 nm.

[0011] In one embodiment, the electrolyte contact angle of the conjugated coordination polymer / ionic liquid composite material is ≥140°.

[0012] Furthermore, in one embodiment, the electrolyte contact angle of the conjugated coordination polymer / ionic liquid composite material is 140°-150°.

[0013] Furthermore, in one embodiment, the electrolyte contact angle of the conjugated coordination polymer / ionic liquid composite material is 144°.

[0014] The second aspect of the present invention is to provide a method for preparing a conjugated coordination polymer / ionic liquid composite material, the method comprising the following steps:

[0015] (1) using water as a solvent, dissolving a metal salt, a conjugated organic ligand, and an ionic liquid, respectively, and ultrasonically homogenizing to obtain solution I, solution II, and solution III;

[0016] (2) mixing solution I, solution II, and solution III, and ultrasonically homogenizing to obtain a reaction precursor solution;

[0017] (3) adding ammonia water to the reaction precursor solution and ultrasonically homogenizing the mixture solution;

[0018] (4) the mixture solution undergoes a coordination chemical reaction under stirring conditions;

[0019] (5) collecting the precipitated product by centrifugation and washing;

[0020] (6) Dry the washed powder.

[0021] In one embodiment, the metal salt in step (1) comprises at least one of ferric chloride, ferric nitrate, cobalt chloride, cobalt nitrate, nickel chloride, nickel nitrate, copper chloride, copper nitrate, zinc chloride, and zinc nitrate, preferably nickel chloride.

[0022] In one embodiment, the conjugated organic ligand in step (1) includes at least one of 1,2,4,5-benzenetetramine tetrahydrochloride, 2,3,6,7,10,11-hexamethylenetriphenylene oxide, 2,5-diamino-1,4-dihydroxybenzene, dopamine hydrochloride, and pyridine.

[0023] In one embodiment, the ionic liquid in step (1) includes at least one of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, N-butylimidazolium bis(trifluoromethylsulfonyl)imide, and 1-carboxybutyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0024] In one embodiment, the molar ratio of the metal salt to the conjugated organic ligand in step (1) is 1:(0.5-1.5), preferably 1:1.

[0025] In one embodiment, in step (1), the mass ratio of the total mass of the metal salt and the conjugated organic ligand to the ionic liquid is 1:(0.05-0.25).

[0026] Furthermore, in one embodiment, the mass ratio of the total mass of the metal salt and the conjugated organic ligand to the ionic liquid is 1:(0.1-0.2), preferably 1:0.25.

[0027] In one embodiment, the concentrations of the metal salt, the conjugated organic ligand and the ionic liquid dissolved in water in step (1) are independently 0.01-0.08 mol·L -1 .

[0028] Furthermore, in one embodiment, the concentrations of the metal salt and the conjugated organic ligand dissolved in water are independently 0.02-0.04 mol·L -1, preferably 0.02 mol·L -1 .

[0029] Furthermore, in one embodiment, the concentration of the ionic liquid dissolved in water is independently 0.03-0.07 mol·L -1 , preferably 0.0314 mol·L -1 .

[0030] In one embodiment, the ultrasonication time in step (1) is 5-30 min, preferably 20 min.

[0031] In one embodiment, the ultrasonication time in step (2) is 10-30 min, preferably 20 min.

[0032] In one embodiment, the amount of ammonia added in step (3) is 5-10 mL / mmol of metal salt, preferably 8 mL.

[0033] In one embodiment, the mass concentration of the ammonia water in step (3) is 25%-28%, preferably 27%.

[0034] In one embodiment, the ultrasonic time in step (3) is 1-3 minutes, preferably 2 minutes.

[0035] In one embodiment, the reaction time in step (4) is 5-12 hours, preferably 10 hours.

[0036] In one embodiment, the centrifugation condition in step (5) is 8000-12000 rpm, and the centrifugation time is 2-5 min, preferably 10000 rpm, and the centrifugation time is 3 min.

[0037] In one embodiment, the washing solvent in step (5) includes at least one of water, ethanol, and acetone.

[0038] Furthermore, in one embodiment, the washing in step (5) comprises washing with water, ethanol, and acetone in sequence.

[0039] Furthermore, in one embodiment, the washing is performed 2-4 times, preferably 3 times. In one embodiment, the drying is performed at 40-80°C in a vacuum oven for 3-10 hours, preferably at 60°C in a vacuum oven for 8 hours.

[0040] The third aspect of the present invention is to provide a conjugated coordination polymer / ionic liquid composite material prepared by the above technical method.

[0041] In one embodiment, the conjugated coordination polymer / ionic liquid composite material has a nanorod morphology with a size of 50-100 nm.

[0042] In one embodiment, the conjugated coordination polymer / ionic liquid composite material is highly ordered and has good crystallinity.

[0043] In one embodiment, the conjugated coordination polymer in the conjugated coordination polymer / ionic liquid composite material is successfully synthesized, and the ionic liquid is successfully introduced into the conjugated coordination polymer to achieve the composite purpose.

[0044] In one embodiment, the electrolyte contact angle of the conjugated coordination polymer / ionic liquid composite material is ≥140°, preferably 140°-150°, and more preferably 144°.

[0045] The fourth aspect of the present invention is to provide a use of the above-mentioned technical method and the conjugated coordination polymer / ionic liquid composite material prepared therefrom, including but not limited to the field of electrocatalytic nitrogen reduction.

[0046] In one embodiment, the conjugated coordination polymer / ionic liquid composite material has a Faradaic efficiency of electrocatalytic nitrogen reduction of ≥38%, and an ammonia yield of ≥240 μg mg -1 h -1 .

[0047] Furthermore, in one embodiment, the conjugated coordination polymer / ionic liquid composite material has a maximum Faradaic efficiency of 38%-45% for electrocatalytic nitrogen reduction, and an ammonia yield of 240-300 μg mg -1 h -1 .

[0048] Furthermore, in one embodiment, the conjugated coordination polymer / ionic liquid composite material has a Faradaic efficiency of 43.6% for electrocatalytic nitrogen reduction and an ammonia yield of 281.6 μg mg -1 h -1 .

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] Previous electrochemical research has focused on sophisticated catalyst design, demonstrating impressive Faradaic efficiencies and ammonia yields. However, achieving both high reactivity and selectivity for practical applications remains challenging. Ionic liquids offer high solubility for various gaseous reactants, enhanced gas diffusion, synergistic catalytic effects, and the ability to inhibit the recombination of active hydrogen species. This invention combines ionic liquids with conjugated coordination polymer catalysts through strong electronic interactions, modifying the catalyst and ultimately regulating the electrode surface microenvironment.

[0051] 2. This invention introduces an ionic liquid into a conjugated coordination polymer, using a one-pot method to synthesize a conjugated coordination polymer / ionic liquid composite material, which exhibits excellent electrocatalytic nitrogen reduction performance. The compound with the ionic liquid optimizes the local environment on the conjugated coordination polymer surface. The introduced ionic liquid itself contains hydrophobic functional groups, which facilitate the creation of a hydrophobic electrode surface microenvironment and inhibit competitive hydrogen evolution reactions. In the resulting conjugated coordination polymer / ionic liquid composite, strong electronic interactions exist between the ionic liquid cations and the conjugated coordination polymer, promoting enhanced catalytic activity for electrocatalytic nitrogen reduction.

[0052] 3. Unlike previous electrochemical research, which focused on sophisticated catalyst design, this invention proposes a strategy for modulating the local environment on the electrode surface by combining the catalyst with an ionic liquid. This provides new insights into the design and regulation of electrocatalysts, a solid step forward for green ammonia synthesis, and offers additional direction for the further development of electrocatalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is a schematic diagram of the preparation process of the conjugated coordination polymer / ionic liquid composite material of the present invention.

[0054] Figure 2 It is a schematic diagram of the reaction structure principle of the conjugated coordination polymer / ionic liquid composite material of the present invention.

[0055] Figure 3 These are scanning electron microscope photos of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1.

[0056] Figure 4 These are the X-ray diffraction spectra of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1, as well as the structural formula of the conjugated coordination polymer material without ionic liquid of Comparative Example 1.

[0057] Figure 5 These are X-ray photoelectron spectra of the F and S elements of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1.

[0058] Figure 6 Graphs showing electrolyte contact angle test results for the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1.

[0059] Figure 7Graph showing the Faradaic efficiency and ammonia yield test results of electrocatalytic nitrogen reduction at different potentials for the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1.

[0060] Figure 8 The Faraday efficiency and yield test results of electrocatalytic nitrogen reduction at the same potential for the conjugated coordination polymer / ionic liquid composite material of Example 1, the conjugated coordination polymer material without ionic liquid in Comparative Example 1, and the conjugated coordination polymer / ionic liquid composite material with an ionic liquid mass fraction of 10 wt% in Example 2 are shown. DETAILED DESCRIPTION

[0061] The present invention provides a high-performance conjugated coordination polymer / ionic liquid composite material and its preparation method and application, belonging to the technical field of conjugated coordination polymer materials. Figure 1 The figure shows a schematic diagram of the preparation process of the conjugated coordination polymer / ionic liquid composite material of the present invention, which mainly includes the following steps:

[0062] (1) A metal salt, a conjugated organic ligand (e.g., 1,2,4,5-benzenetetramine tetrahydrochloride), and an ionic liquid (e.g., 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) are ultrasonically dispersed in water to obtain solution I, solution II, and solution III, respectively;

[0063] (2) mixing the three solutions uniformly to obtain a reaction precursor solution;

[0064] (3) adding ammonia to promote the coordination between the metal salt and the conjugated organic ligand;

[0065] (4) reacting the mixture under stirring conditions to allow the ionic liquid to be fully compounded by physical blending;

[0066] (5) collecting the precipitated product by centrifugation and washing;

[0067] (6) Drying the washed powder to obtain a conjugated coordination polymer / ionic liquid composite material.

[0068] like Figure 2 The figure shows a schematic diagram of the reaction structure principle of the conjugated coordination polymer / ionic liquid composite material of the present invention. The strong electronic interaction between the ionic liquid and the conjugated coordination polymer in the obtained conjugated coordination polymer / ionic liquid composite material enables the ionic liquid and the conjugated coordination polymer to be tightly bound, thereby realizing the construction of a hydrophobic electrode surface microenvironment, so that it has high catalytic activity for the electrocatalytic nitrogen reduction reaction.

[0069] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0070] Unless otherwise specified, the sources of the reagents used in the examples of the present invention can be purchased from the market.

[0071] The present invention provides a characterization test result diagram of Example 1. The other embodiments all adopt the same characterization test method. Those skilled in the art can directly and unambiguously determine the content of the embodiments of the present invention through the characterization test method provided by the present invention, which will not be elaborated here.

[0072] Example 1: Preparation of conjugated coordination polymer / ionic liquid composite material

[0073] (1) Weigh 240.09 mg (1 mmol) of nickel chloride hexahydrate and dissolve it in 50 mL of water to obtain a light green solution I; weigh 292.80 mg (1 mmol) of 1,2,4,5-benzenetetramine tetrahydrochloride and dissolve it in 40 mL of water to obtain a dark purple solution II; weigh 133.22 mg (0.314 mmol) of the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and evenly disperse it in 10 mL of water to obtain a white emulsion III. The ionic liquid content in the total mass of the metal salt, conjugated organic ligand, and ionic liquid is 20 wt%.

[0074] (2) The light green solution I, the dark purple solution II, and the white emulsion III were mixed to obtain a dark purple reaction precursor solution, which was ultrasonically dispersed for 20 minutes.

[0075] (3) 8 mL of aqueous ammonia was added dropwise to the reaction precursor solution obtained in step (2). During the addition, the solution was observed to turn black. The mixed solution was then ultrasonically dispersed for 1 min.

[0076] (4) Turn on the stirring device and set the speed to 200 r / min. Stir the mixed solution obtained in step (3) at room temperature for 10 hours to carry out the coordination chemical reaction.

[0077] (5) The precipitate obtained in step (4) was collected by centrifugation and washed three times with water, ethanol, and acetone respectively. The centrifugal speed was set to 10,000 rpm and the centrifugation time was 3 minutes.

[0078] (6) The black precipitate obtained after centrifugation was placed in a vacuum oven and dried under vacuum at 60°C for 8 h until the solvent was completely evaporated. The obtained solid was crushed to obtain catalyst powder.

[0079] Comparative Example 1: Preparation of conjugated coordination polymer material without ionic liquid

[0080] (1) Weigh 240.09 mg (1 mmol) of nickel chloride hexahydrate and dissolve it in 50 mL of water to obtain a light green solution I. Weigh 292.80 mg (1 mmol) of 1,2,4,5-benzenetetramine tetrahydrochloride and dissolve it in 50 mL of water to obtain a dark purple solution II.

[0081] (2) The light green solution I and the dark purple solution II were mixed to obtain a dark purple reaction precursor solution, which was then ultrasonically dispersed for 20 min.

[0082] (3) 8 mL of aqueous ammonia was added dropwise to the reaction precursor solution obtained in step (2). During the addition, the solution was observed to turn black. The mixed solution was then ultrasonically dispersed for 1 min.

[0083] (4) Turn on the stirring device and set the speed to 200 r / min. Stir the mixed solution obtained in step (3) at room temperature for 10 hours to carry out the coordination chemical reaction.

[0084] (5) The precipitate obtained in step (4) was collected by centrifugation and washed three times with water, ethanol, and acetone respectively. The centrifugal speed was set to 10,000 rpm and the centrifugation time was 3 minutes.

[0085] (6) The black precipitate obtained after centrifugation was placed in a vacuum oven and dried under vacuum at 60°C for 8 h until the solvent was completely evaporated. The obtained solid was crushed to obtain catalyst powder.

[0086] Example 2: Preparation of conjugated coordination polymer / ionic liquid composite material

[0087] (1) Weigh 240.09 mg (1 mmol) of nickel chloride hexahydrate and dissolve it in 50 mL of water to obtain a light green solution I; weigh 292.80 mg (1 mmol) of 1,2,4,5-benzenetetramine tetrahydrochloride and dissolve it in 40 mL of water to obtain a dark purple solution II; weigh 59.21 mg (0.140 mmol) of the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and evenly disperse it in 10 mL of water to obtain a white emulsion III. The ionic liquid content in the total mass of the metal salt, conjugated organic ligand, and ionic liquid is 10 wt%.

[0088] (2) The light green solution I, the dark purple solution II, and the white emulsion III were mixed to obtain a dark purple reaction precursor solution, which was ultrasonically dispersed for 20 minutes.

[0089] (3) 8 mL of aqueous ammonia was added dropwise to the reaction precursor solution obtained in step (2). During the addition, the solution was observed to turn black. The mixed solution was then ultrasonically dispersed for 1 min.

[0090] (4) Turn on the stirring device and set the speed to 200 r / min. Stir the mixed solution obtained in step (3) at room temperature for 10 hours to carry out the coordination chemical reaction.

[0091] (5) The precipitate obtained in step (4) was collected by centrifugation and washed three times with water, ethanol, and acetone respectively. The centrifugal speed was set to 10,000 rpm and the centrifugation time was 3 minutes.

[0092] (6) The black precipitate obtained after centrifugation was placed in a vacuum oven and dried under vacuum at 60°C for 8 h until the solvent was completely evaporated. The obtained solid was crushed to obtain catalyst powder.

[0093] Example 3: Preparation of conjugated coordination polymer / ionic liquid composite material

[0094] (1) Weigh 240.09 mg (1 mmol) of nickel chloride hexahydrate and dissolve it in 25 mL of water to obtain a light green solution I; weigh 292.80 mg (1 mmol) of 1,2,4,5-benzenetetramine tetrahydrochloride and dissolve it in 20 mL of water to obtain a dark purple solution II; weigh 133.22 mg (0.314 mmol) of the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and evenly disperse it in 5 mL of water to obtain a white emulsion III. The ionic liquid content in the total mass of the metal salt, conjugated organic ligand, and ionic liquid is 20 wt%. The difference from Example 1 is that the solubility concentration in water is different.

[0095] (2) The light green solution I, the dark purple solution II, and the white emulsion III were mixed to obtain a dark purple reaction precursor solution, which was ultrasonically dispersed for 20 minutes.

[0096] (3) 8 mL of aqueous ammonia was added dropwise to the reaction precursor solution obtained in step (2). During the addition, the solution was observed to turn black. The mixed solution was then ultrasonically dispersed for 1 min.

[0097] (4) Turn on the stirring device and set the speed to 200 r / min. Stir the mixed solution obtained in step (3) at room temperature for 10 hours to carry out the coordination chemical reaction.

[0098] (5) The precipitate obtained in step (4) was collected by centrifugation and washed three times with water, ethanol, and acetone respectively. The centrifugal speed was set to 10,000 rpm and the centrifugation time was 3 minutes.

[0099] (6) The black precipitate obtained after centrifugation was placed in a vacuum oven and dried under vacuum at 60°C for 8 h until the solvent was completely evaporated. The obtained solid was crushed to obtain catalyst powder.

[0100] Experimental example: Structural characterization and performance testing of conjugated coordination polymer / ionic liquid composites

[0101] In this experimental example, relevant performance tests were conducted on the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid in Comparative Example 1, mainly including scanning electron microscopy test, X-ray diffraction spectrum test, Fourier transform infrared spectrum test, X-ray photoelectron spectroscopy test, electrolyte contact angle test and electrocatalytic nitrogen reduction performance test. The results are as follows:

[0102] Figure 3 Shown are scanning electron micrographs of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1. It can be seen that the samples of Example 1 and Comparative Example 1 both have nanorod-like morphology with a size of about 50-100 nm.

[0103] Figure 4 Figure a shows the X-ray diffraction spectra of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid of Comparative Example 1. It can be seen that the two materials have the same crystal phase, good crystallinity, and are highly ordered. Characteristic peaks are found at 2θ = 14.4°, 20.7°, 23.8°, 29.3°, 40.0°, and 44.2° in Example 1 and Comparative Example 1, corresponding to the (011), (021), (030), (022), (042), and (033) reflection planes, respectively. These characteristic peaks can be used to confirm the successful synthesis of the conjugated coordination polymer material.

[0104] Figure 5 Figure a shows the F element X-ray photoelectron spectra of the conjugated coordination polymer / ionic liquid composite material from Example 1 and the conjugated coordination polymer material from Comparative Example 1, which does not contain an ionic liquid. It can be seen that the conjugated coordination polymer / ionic liquid composite material exhibits an F1s peak compared to the conjugated coordination polymer material without an ionic liquid. Since the conjugated coordination polymer itself does not contain F, the presence of F in the added ionic liquid, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, indicates successful introduction of the ionic liquid. Figure 5Figure b shows the S-element X-ray photoelectron spectra of the conjugated coordination polymer / ionic liquid composite material from Example 1 and the conjugated coordination polymer material from Comparative Example 1, which does not contain an ionic liquid. It can be seen that the conjugated coordination polymer / ionic liquid composite material exhibits an S2p peak compared to the conjugated coordination polymer material without an ionic liquid. Since the conjugated coordination polymer itself does not contain the S element, the presence of S in the added ionic liquid, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, indicates successful introduction of the ionic liquid.

[0105] Figure 6 Shown are the electrolyte contact angle test results for the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without an ionic liquid in Comparative Example 1. It can be seen that the introduction of the ionic liquid reduces the electrolyte affinity of the conjugated coordination polymer material, increasing the contact angle from 134° to 144°, which helps create a more hydrophobic electrode surface microenvironment and inhibits the competitive hydrogen evolution reaction.

[0106] Figure 7 Figure a shows the Faraday efficiency test results of the electrocatalytic nitrogen reduction of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid in Comparative Example 1 at different potentials. It can be seen that the introduction of ionic liquid improves the electrocatalytic nitrogen reduction activity of the conjugated coordination polymer material, thereby improving its Faraday efficiency. When the potential is -0.15 to -0.3V, the Faraday efficiency of the conjugated coordination polymer / ionic liquid composite material is significantly improved compared to the conjugated coordination polymer material without ionic liquid. In particular, when the potential is -0.2V, the conjugated coordination polymer / ionic liquid composite material has the highest Faraday efficiency (43.6%), which is better than the conjugated coordination polymer material without ionic liquid (30.9%). Figure 7 b is the test result of ammonia yield under different potentials for the electrocatalytic nitrogen reduction of the conjugated coordination polymer / ionic liquid composite material of Example 1 and the conjugated coordination polymer material without ionic liquid in Comparative Example 1. It can be seen that when the potential is -0.15 to -0.3V, the introduction of ionic liquid improves the electrocatalytic nitrogen reduction activity of the conjugated coordination polymer material, thereby improving its ammonia yield. In particular, when the potential is -0.2V, the conjugated coordination polymer / ionic liquid composite material has the highest ammonia yield (281.6μg mg -1 h -1 ), which is better than the conjugated coordination polymer material without ionic liquid (182.4 μg mg -1 h -1 ).

[0107] Figure 8The graph shows the Faradaic efficiency and yield test results for the electrocatalytic nitrogen reduction of the conjugated coordination polymer / ionic liquid composite of Example 1 and the conjugated coordination polymer material without ionic liquid from Comparative Example 1. As can be seen, the Faradaic efficiency and ammonia yield of the conjugated coordination polymer / ionic liquid composite exhibit a volcanic pattern with increasing ionic liquid content, with both increasing Faradaic efficiency and ammonia yield increasing with increasing ionic liquid content. The electrocatalytic nitrogen reduction performance of the catalyst is optimal when the ionic liquid content is 20 wt%, while the performance decreases when the ionic liquid content exceeds 20 wt%.

[0108] It should be noted that the above is only a preferred embodiment of the present invention. It should be pointed out that those skilled in the art can make several improvements and modifications without departing from the principles of the present invention, and such improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A conjugated coordination polymer / ionic liquid composite material, characterized in that: The conjugated coordination polymer / ionic liquid composite material is formed by combining a conjugated coordination polymer and an ionic liquid through strong electronic interaction, wherein: The conjugated coordination polymer is constructed by metal single atoms and conjugated organic ligands, wherein the metal single atoms include at least one of iron, cobalt, nickel, copper and zinc, and the conjugated organic ligands include at least one of 1,2,4,5-benzenetetramine tetrahydrochloride, 2,3,6,7,10,11-hexamethylenetriphenyl, 2,5-diamino-1,4-dihydroxybenzene, dopamine hydrochloride and pyridine. The ionic liquid includes at least one of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, N-butylimidazolium bis(trifluoromethylsulfonyl)imide, and 1-carboxybutyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

2. The conjugated coordination polymer / ionic liquid composite material according to claim 1, characterized in that: The conjugated coordination polymer / ionic liquid composite material has a nanorod morphology with a size of 50-100 nm; and / or Preferably, the electrolyte contact angle of the conjugated coordination polymer / ionic liquid composite material is ≥140°, preferably 140°-150°.

3. A method for preparing a conjugated coordination polymer / ionic liquid composite material, characterized in that: The following steps are involved: (1) using water as a solvent, dissolving a metal salt, a conjugated organic ligand, and an ionic liquid, respectively, and ultrasonically homogenizing to obtain solution I, solution II, and solution III; (2) mixing the solution I, solution II, and solution III, and ultrasonically homogenizing to obtain a reaction precursor solution; (3) adding aqueous ammonia to the reaction precursor solution and performing ultrasonic homogenization to obtain a mixture solution; (4) the mixture solution undergoes a coordination chemical reaction under stirring conditions; (5) collecting the precipitated product by centrifugation and washing; (6) Drying the washed powder.

4. The method according to claim 3, characterized in that The metal salt in step (1) comprises at least one of ferric chloride, ferric nitrate, cobalt chloride, cobalt nitrate, nickel chloride, nickel nitrate, copper chloride, copper nitrate, zinc chloride and zinc nitrate; and / or Preferably, the conjugated organic ligand in step (1) comprises at least one of 1,2,4,5-benzenetetramine tetrahydrochloride, 2,3,6,7,10,11-hexamethylenetriphenyl, 2,5-diamino-1,4-dihydroxybenzene, dopamine hydrochloride and pyridine; and / or Preferably, the ionic liquid in step (1) comprises at least one of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, N-butylimidazolium bis(trifluoromethylsulfonyl)imide, and 1-carboxybutyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; and / or Preferably, in step (1), the molar ratio of the metal salt to the conjugated organic ligand is 1:(0.5-1.5); and / or Preferably, in step (1), the mass ratio of the total mass of the metal salt, the conjugated organic ligand and the ionic liquid to the mass ratio of the ionic liquid is 1:(0.05-0.25), preferably 1:(0.1-0.2), preferably 1:0.2; and / or Preferably, in step (1), the concentrations of the metal salt, the conjugated organic ligand and the ionic liquid dissolved in water are independently 0.01-0.08 mol·L -1 , Preferably, the concentration of the metal salt and the conjugated organic ligand dissolved in water is independently 0.02-0.04 mol·L -1 , preferably 0.02 mol·L -1 ; and / or Preferably, the concentration of the ionic liquid dissolved in water is independently 0.03-0.07 mol·L -1 , preferably 0.0314 mol·L -1 ; and / or Preferably, the ultrasonic time in step (1) is 5-30 min.

5. The method according to claim 3, characterized in that: The ultrasonic time in step (2) is 10-30 min.

6. The method according to claim 3, characterized in that The mass concentration of ammonia water in step (3) is 25%-28%; and / or The amount of ammonia added in step (3) is 5-10 mL / mmol of metal salt, preferably 8 mL; and / or Preferably, the ultrasonic time in step (3) is 1-3 min.

7. The method according to claim 3, characterized in that The reaction time in step (4) is 5-12 hours.

8. The method according to claim 3, characterized in that The centrifugation condition in step (5) is 8000-12000 rpm, and the centrifugation time is 2-5 min; and / or Preferably, the washing solvent in step (5) comprises at least one of water, ethanol and acetone, and / or Preferably, the washing comprises washing with water, ethanol and acetone in sequence, and / or Preferably, the washing number is 2-4 times.

9. The method according to claim 3, characterized in that: The drying conditions in step (6) are 40-80° C. and vacuum drying in an oven for 3-10 hours.

10. A use of the conjugated coordination polymer / ionic liquid composite material as claimed in claim 1 or 2, or the conjugated coordination polymer / ionic liquid composite material prepared by the method according to any one of claims 3 to 9, including application in the fields of catalysis, adsorption, sensing, electrochemical energy storage, electromagnetic shielding or wave absorption; and / or Preferably, the Faradaic efficiency of the conjugated coordination polymer / ionic liquid composite material for electrocatalytic nitrogen reduction is ≥38%, and the ammonia yield is ≥240 μg mg -1 h -1 .